FATIGUE STUDY OF A CIRCULAR SAW SHAFT WITH COSMOSWORKS (Innovation in Woodworking Industry and Engineering design, 2026)
In the last few years systematic fatigue studies are carrying out in Faculty of Forest Industry. Fatigue analysis of a 3D-model of circular saw shaft is carried out by finite elements method (FEA) with CosmosWorks on the base of the fatigue curve (S-N curve) for carbon steel 45. Different fatigue events are studied – with constant amplitude (stress ratio R=-1) and with changeable amplitude. Plots for total life and damage, rainflow 3-D histograms and damage 3-D histograms are obtained.